2022-RA-883-ESGO Rare Cancers in Gynecologic Oncology, ENGOT initiative for a European Registry. (20th October 2022) - Ceppi, Lorenzo; Bergamini, Alice; Biagioli, Elena; Solheim, Olesya; González-Martín, Antonio; Ottevanger, Nelleke; van Nieuwenhuysen, Els; Hasenburg, Annette; Cadoo, Karen; Braicu, Elena Ioana; Hall, Marcia; Bauerschlag, Dirk; et al.
Abstract : Introduction/Background: Management of rare cancers is challenging due to limited data, experience, low referral rates to oncological centers, and the fact that most treatments can only be based on experts' opinions. Many gynecologic malignancies are considered rare diseases due to their low incidence. The European Commission has highlighted the need for treatment standardization in rare cancers, suggesting the creation of international networks and registries. Our purpose is to create an international European registry for the collection of data on rare gynecologic cancers. Methodology: This is a multi-center, international, retrospective, and prospective observational study collecting data of patients with rare gynecological cancers in centers among the European Network of Gynecological Oncological Trial Group (ENGOT). In its initial development, the study includes patients with malignant germ cell tumors, sex-cord stromal tumors, and low-grade serous tumors of the ovary, and can be expanded to other rare gynecological cancers. The aim is to collect complete clinical, surgical, and pathology data. The follow-up of patients will continue for up to 20 years. REDCap (Research Electronic Data Capture) web application will be used for data collection. A survey was conducted in order to assess interests and issues among the representatives of each ENGOT collaborative group. Periodical meetings were set up in order to update the ENGOT rare tumor working group on database development and share critical points. Results: The survey showed an interest in adopting the database in 94.4% of responders. The database has been developed, revised by a reviewers committee, and shared for data entry. Conclusion: National collaborative groups will participate independently in setting up a REDCap-based database with the same database structure. A central ENGOT coordination will ensure the appropriate data entry and registry management for future data analysis. This project will allow improving the knowledge of these rare cancers in Europe.